2018
DOI: 10.1177/0886260518803610
|View full text |Cite
|
Sign up to set email alerts
|

Digital Intimate Partner Violence Among Peruvian Youths: Validation of an Instrument and a Theoretical Proposal

Abstract: The present study presents psychometric information on a new instrument, the Digital Intimate Partner Violence Questionnaire (DIPVQ), and explores the similitudes and differences between in-person and digital-based abuses (those that involve the use of information and communication technologies [ICTs]). In all, 449 Peruvian students took part in the study ( X = 21.2 years; SD = 4.3 years; 73% women). DIPVQ structure was determined by carrying out an exploratory factor analysis (EFA) with polychoric correlation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…Clearly, control behaviors are more frequent than direct aggression. These found patterns are similar to those reported by Borrajo et al (2015) and, as well, differentiations made by others (e.g., López-Cepero et al, 2018) between control-centered and damage-centered abuse. The dimensionality of the CDAQ, which permits differentiating between control and direct aggression, could help us to understand the range of prevalence found in previous research.…”
Section: Discussionsupporting
confidence: 91%
“…Clearly, control behaviors are more frequent than direct aggression. These found patterns are similar to those reported by Borrajo et al (2015) and, as well, differentiations made by others (e.g., López-Cepero et al, 2018) between control-centered and damage-centered abuse. The dimensionality of the CDAQ, which permits differentiating between control and direct aggression, could help us to understand the range of prevalence found in previous research.…”
Section: Discussionsupporting
confidence: 91%
“…Most studies presented the results of the measurement properties in relation to content validity, structural validity and internal consistency (Table 2). Only four studies evaluated reliability (Começanha & Maia, 2018;Hokoda et al, 2006;Soriano-Ayala et al, 2021;Wolfe et al, 2001), and 13 studies evaluated the hypotheses testing for construct validity (Al-Modallal et al, 2020;Bledsoe & Sar, 2011;Borrajo et al, 2015;Começanha & Maia, 2018;Demirtas et al, 2018;He et al, 2013;López-Cepero et al, 2021;Muñoz-Rivas et al, 2019;Rey-Anacona et al, 2019;Rothman et al, 2021;Wolfe et al, 2001;Wong et al, 2018;Yakubovich et al, 2019). Regarding the criterion validity, the studies (N = 10) that evaluated this property took a different gold standard: CADRI (Aizpitarte et al, 2017;Emelianchik-Key et al, 2018;Fernández-González et al, 2012;Morelli et al, 2018;Rothman et al, 2021); CTS (Bledsoe & Sar, 2011) and CTS2 (Demirtas et al, 2018;Ureña et al, 2015) as a reference, or population samples that had been victims of violence (Começanha & Maia, 2018;Wong et al, 2018).…”
Section: Results Of Measurement Propertiesmentioning
confidence: 99%
“…Ten instruments (28.6%), CADRI/Spanish version, CTS2/deaf students, DIPVQ, IPVCS, IPV‐ALSPAC, MARSHA, MPAB, SCIRS, SDPVVS, TSDV and VADRI carried out an exploratory factor analysis (EFA) without confirming the structure of their factors, confirmatory factor analysis (CFA) (Aizpitarte et al, 2017; Al‐Modallal et al, 2020; Anderson & Leigh, 2010; Bledsoe & Sar, 2011; Fernández‐Fuertes et al, 2006; Follingstad et al, 2015; He et al, 2013; López‐Cepero et al, 2021; Rothman et al, 2021; Yakubovich et al, 2019). The methodological quality of most of these instruments was evaluated as ‘adequate’ because they reported the Kaiser–Meyer–Olkin (KMO), Barlett's test of sphericity, a number of factors that explained a certain percentage of the variance for the resulting items, sample size; in addition, the chosen model fitted the research question.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have indicated that there is an overlap between online and offline victimization (Gómez-Baya et al 2019;Kaakinen et al 2018;Maas et al 2019;López-Cepero et al 2018;Marganski and Melander 2018;Nedelec 2018;Wright et al 2019). This is a consequence of the fact that most people are exposed to risks in the offline world as well as in the cyberspace.…”
Section: Online and Offline Victimizationmentioning
confidence: 99%